2021
DOI: 10.1371/journal.pone.0253021
|View full text |Cite|
|
Sign up to set email alerts
|

A real-world evaluation of radium-223 in combination with abiraterone or enzalutamide for the treatment of metastatic castration-resistant prostate cancer

Abstract: Introduction Radium-223, abiraterone, and enzalutamide have each been shown to significantly improve survival as monotherapy in patients with metastatic castration-resistant prostate cancer. However, effects of combination radium-223 plus abiraterone or enzalutamide on survival and safety remain unclear. Patients and methods This single-center retrospective cohort study used electronic health record data of patients with metastatic castration-resistant prostate cancer and bone metastases who were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…When 223 Ra monotherapy was compared with standardof-care, the estimated 36-month fracture risk in the respective groups was 19% vs. 10% (HR 1.61; 95% CI: 0.96-3.02) (43). Regimens combining use of 223 Ra and abiraterone (plus prednisolone) or enzalutamide have been reported in real-world studies (44)(45)(46)(47)(48). However, based on a significantly increased risk of fractures when 223 Ra was used in combination with abiraterone plus prednisolone in the ERA 223 phase 3 RCT (49), this combination is now contraindicated in the EU (2) and is not recommended in the US (3).…”
Section: Safetymentioning
confidence: 99%
“…When 223 Ra monotherapy was compared with standardof-care, the estimated 36-month fracture risk in the respective groups was 19% vs. 10% (HR 1.61; 95% CI: 0.96-3.02) (43). Regimens combining use of 223 Ra and abiraterone (plus prednisolone) or enzalutamide have been reported in real-world studies (44)(45)(46)(47)(48). However, based on a significantly increased risk of fractures when 223 Ra was used in combination with abiraterone plus prednisolone in the ERA 223 phase 3 RCT (49), this combination is now contraindicated in the EU (2) and is not recommended in the US (3).…”
Section: Safetymentioning
confidence: 99%
“…A total of 364 potentially relevant articles were identified from our search, and 10 articles (consisting of 2835 patients) were subsequently enrolled in the meta-analysis. 5 7 , 9 , 15 , 24 28 The detailed steps of the literature search are shown in . These articles included four RCTs, five retrospective cohort studies (RCSs), and one single-arm trial.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 However, other studies and meta-analyses indicate that the combination of radium-223 and AR-targeted therapy is effective, and the risk of fracture can be reduced by concomitant use of BHAs such as denosumab or zoledronic acid. [24][25][26][27][28][29][30][31] The ongoing…”
Section: Discussionmentioning
confidence: 99%
“…The ERA‐223 study indicated increased risk of fracture when abiraterone acetate and radium‐223 were used together versus abiraterone alone, 21 resulting in regulatory restrictions on this combination 22,23 . However, other studies and meta‐analyses indicate that the combination of radium‐223 and AR‐targeted therapy is effective, and the risk of fracture can be reduced by concomitant use of BHAs such as denosumab or zoledronic acid 24–31 . The ongoing phase 3 PEACE III study (NCT02194842) will assess the efficacy and safety of radium‐223 combined with enzalutamide.…”
Section: Discussionmentioning
confidence: 99%